2012
DOI: 10.1186/1423-0127-19-103
|View full text |Cite
|
Sign up to set email alerts
|

The anti-malarial drug Mefloquine disrupts central autonomic and respiratory control in the working heart brainstem preparation of the rat

Abstract: BackgroundMefloquine is an anti-malarial drug that can have neurological side effects. This study examines how mefloquine (MF) influences central nervous control of autonomic and respiratory systems using the arterially perfused working heart brainstem preparation (WHBP) of the rat. Recordings of nerve activity were made from the thoracic sympathetic chain and phrenic nerve, while heart rate (HR) and perfusion pressure were also monitored in the arterially perfused, decerebrate, rat WHBP. MF was added to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…My colleagues and I have also shown that mefloquine, which can block connexin 36‐containing gap junctions, reduces the sympathoexcitation due to chemoreceptor activation via supraspinal pathways in the working heart–brainstem preparation (Lall et al . ; Fig. D ).…”
Section: Introductionmentioning
confidence: 83%
“…My colleagues and I have also shown that mefloquine, which can block connexin 36‐containing gap junctions, reduces the sympathoexcitation due to chemoreceptor activation via supraspinal pathways in the working heart–brainstem preparation (Lall et al . ; Fig. D ).…”
Section: Introductionmentioning
confidence: 83%
“…Blockade of gap junctions reduces or even abolishes ongoing network oscillations in a spinal cord slice preparation, indicating that these electrical synapses may contribute to the overall co-ordinated output in the sympathetic nerves (Pierce et al, 2010, figure 2C. We have further shown that mefloquine, which can block connexin 36 containing gap junctions, reduces the sympathoexcitation due to chemoreceptor activation via supraspinal pathways in the working heart brainstem preparation (Lall et al, 2012, figure 2D). Mefloquine can have effectsat other sites, including potassium and calcium channels (see (Pierce et al, 2010) for discussion) so a better approach is to use transgenic animals that better target these gap junctions.…”
Section: Gap Junctions In Sympathetic Circuitsmentioning
confidence: 82%
“…However, connexin 36 immunoreactivity is abundant in adult rats, as evidenced by our own use of Cx36 reporter mice and immunohistochemical data (Marina et al, 2008) and spikelets have been reported in adult SPNs (see (Stalbovskiy et al, 2014) for discussion). The robust effects of the gap junction blocker mefloquine in six week old rats (Lall et al, 2012) suggest that they are functional at this age and are contributing to ongoing activity. Moreover, the incidence of spikelets did not change with age in the working heart brainstem preparation (Stalbovskiy et al, 2014).…”
Section: Gap Junctions In Sympathetic Circuitsmentioning
confidence: 99%
“…There is still debate over the contribution of GJs to SPN coordinated activity in adults because some consider that GJ expression in these neurons is a developmental phenomenon (5) and thus may not contribute to sympathetic outflow in adults. However, the Cx36 protein is immunohistochemically detected in SPNs in adult rat (8), and pharmacologic blockade of Cx36‐containing GJs influenced sympathetic variables in rats aged 4 to 6 wk (10). Furthermore, GJ coupling between SPNs in adult spinal cord slices was reported in a brief communication (30), while in the WHBP of increasing age from P5 to P16, there is no reduction in the number of SPNs that exhibit spikelets (28).…”
Section: Discussionmentioning
confidence: 99%
“…; Alfa Aesar, Lancaster, United Kingdom) before being deeply anesthetized with halothane. Working heart–brain stem preparations (WHBPs) were surgically prepared as previously described (10, 11); briefly, after submerging the head and thorax in ice‐cold artificial (a) CSF, decerebration at the precollicular level was followed by skinning; then the phrenic and sympathetic nerves were isolated and the diaphragm, lungs, and surrounding organs removed. After removal to a recording chamber, the descending aorta was cannulated and perfused retrogradely with aCSF.…”
Section: Methodsmentioning
confidence: 99%